2019
DOI: 10.1039/c9cp02348h
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of RIr3 (R = Gd, Tb, Ho) compounds with coexisting polymorphic phases

Abstract: The binary compounds GdIr3, TbIr3 and HoIr3 are synthesized successfully and found to form in macroscopic co-existence of two polymorphic phases: C15b and AuCu3-type. The dc magnetization and heat capacity studies confirm that C15b phase orders ferromagnetically, whereas the AuCu3 phase remains paramagnetic down to 2 K. The frequency dependent ac-susceptibility data, time dependent magnetic relaxation behavior and magnetic memory effect studies suggest that TbIr3 and HoIr3 are cannonical spin-glass system, but… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…Taking cues from the earlier reported results in some other members of RIr 3 (R = Gd, Tb, Dy, Ho, Er) series of compounds, 35−37 we have restricted p AuCu 3 to 0 K. The fitting yields p AuBe 5 = 7 K, which is very close to the T C of the material. Moreover, as GdIr 3 forms in the AuBe 5 -type structure, it exhibits ferromagnetic ordering at ∼83 K, 35 deGennes scaling suggests that the NdIr 3 , forming in the same structure, should exhibit Curie temperature ∼ 9.62 K (=0.116 × 83 K), which is close to our experimentally reported value (10 K). Matching of theoretically estimated Weiss temperature with the experimentally observed Curie temperature confirms that the AuBe 5 -type phase only contributes to the magnetic order.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Taking cues from the earlier reported results in some other members of RIr 3 (R = Gd, Tb, Dy, Ho, Er) series of compounds, 35−37 we have restricted p AuCu 3 to 0 K. The fitting yields p AuBe 5 = 7 K, which is very close to the T C of the material. Moreover, as GdIr 3 forms in the AuBe 5 -type structure, it exhibits ferromagnetic ordering at ∼83 K, 35 deGennes scaling suggests that the NdIr 3 , forming in the same structure, should exhibit Curie temperature ∼ 9.62 K (=0.116 × 83 K), which is close to our experimentally reported value (10 K). Matching of theoretically estimated Weiss temperature with the experimentally observed Curie temperature confirms that the AuBe 5 -type phase only contributes to the magnetic order.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…It was also pointed out in the literature that the stability of NdIr 3 , GdIr 3 , and DyIr 3 compounds lie at the borderline of the said two (AuCu 3 - and PuNi 3 -type) crystal structures. It should also be noted that a few RIr 3 (R = Gd, Tb, Dy, Ho, and Er) compounds have also been reported to form as a rare coexistence of two polymorphic structures of AuCu 3 -type and a newer structure of AuBe 5 -type (reported earlier for RRh 3 and RPt 3 compounds) that was never predicted for any RIr 3 compounds (Figure ). It was also reported that while AuBe 5 -type RIr 3 (R = Gd, Tb, Dy, Ho, and Er) compounds mentioned above exhibit ferromagnetic ordering at low temperatures, their AuCu 3 -type polymorphic counterparts remain paramagnetic down to 2.5 K. Another recent report on PuNi 3 -type NdIr 3 , formed after annealing at 1350 °C for 36 h and again at 1370 °C for 36 h under high vacuum, suggested the ferromagnetic ground state for that phase as well .…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…[ 13 ] Moreover, S. Mondal and coworkers have performed an experimental work using X‐ray diffraction (XRD) and resistivity measurements of Ru 2 VAl and Ru 2 VGa. [ 14 ] On the other hand, they have reported in a similar work the structural and thermal properties, as well as the electrical resistivity, of the same compounds. [ 15 ] More recently, I. H. Bhat and D. C. Gupta computed the magnetic and electronic characterization of Ru 2 VGe, and Ru 2 VSb Heusler alloys have been studied using the ab initio method within the GGA scheme.…”
Section: Introductionmentioning
confidence: 89%
“…[ 14 ] On the other hand, they have reported in a similar work the structural and thermal properties, as well as the electrical resistivity, of the same compounds. [ 15 ] More recently, I. H. Bhat and D. C. Gupta computed the magnetic and electronic characterization of Ru 2 VGe, and Ru 2 VSb Heusler alloys have been studied using the ab initio method within the GGA scheme. [ 16 ] After our careful search of the literature, there is no experimental work or theoretical research available concerning Ru 2 VGe 0.5 Sb 0.5 Heusler quaternary alloy, which represents the fusion between the Ru 2 VGe and Ru 2 VSb ternary compounds.…”
Section: Introductionmentioning
confidence: 93%